Medicinal plants in the process air disinfection of poultry houses - Свінтицька, К. В. (Scientific Progress & Innovations, 2013)
The possibility of using officinal plants during air disinfection of poultry houses has been given. Essential oils of officinal plants have a wide range of antimicrobic action against many pathogens and immunocorrective properties which assist reducing morbidity and increasing poultry productivity and safety. The mechanism of antimicrobic action of such officinal plants as peppermint, garden sage, and fennel was studied during the experiment. The doses of essential oils which help to reduce bacterial air contamination were determined.